Di Bawah Tekanan Kapitalisme Perkebunan: Pertumbuhan dan Radikalisasi Sarekat Ra’jat Tegal 1923-1926 - Wijanarto Wijanarto (Jurnal Sejarah Citra Lekha, 2016)
This article examines on the radicalization growth of Sarekat Ra’jat (SR) in several factors as its key influence. The one factor interrelated on radicalization was the existence of sugar industry in Tegal. It views on linkages between the sugar industry with the development of SR and its influence indicators of radicalization. This condition was part of the communist partij’s expansion. The development of SR shows suprisingly number of members. SR Tegal reached 5327 peoples as their members. The total membership evenly came from all areas, especially close to the sugar industry in Pangkah, Pagongan, Kemanglen, Adiwerna and Balapoelang. It was the main reason to make the Dutch government to striccht oversight the administrative and appled legal sanctions. The SR resistance was took-placed at Karangcegak in 1926, effected the undiscipline and sporadic resistance of the members. It made the Dutch government easy to suppress and acted tough. The trial rebellion conducted by SR in Karangcecek, but it was failed. However it was not effect the eagerness to re-against  PKI in November 1926. The revolutionary in Tegal option was chosed as result.